Pre-school children who are frequent attenders in Emergency Departments: an observational study of associated demographics and clinical characteristics - Blair,M; Poots,A; Lim,V; Hiles,S; Greenfield,G; Crehan,C; Kugler,B; Boreham,C (Archives of Disease in Childhood, 2017)
Background: Unscheduled visits to emergency departments (ED) have increased in the UK in recent years. Children who are repeat attenders are relatively understudied. Aims: To describe the socio-demographic and clinical characteristics of pre-schoolers who attend ED a large District General Hospital.Method/Study Design: Observational study analysing routinely collected ED operational data. Children attending 4 or more visits per year were considered as “frequent attenders”. Poisson regression was used with demographic details (age, sex, ethnicity, socio-demographic status), to predict number of attendances seen in the year. We further analysed detailed diagnostic characteristics of a random sample of 10% of attendees. Main findings: 10,169 patients visited in the 12 month period with 16,603 attendances. 655 individuals attended on 3,335 occasions. 6.4% of this population accounted for 20.1% of total visits. In the 10% sample, there were 304 attendances, and 69(23%) had an underlying chronic longstanding illness. This group were 2.4 times more likely to be admitted as in-patients compared to those without such conditions , median length of stay of 6.2 hours vs. 2.5 hrs (p=NS).Conclusions: Frequent ED attenders fall broadly into two distinct clinical groups: those who habitually return with self- limiting conditions and those with or without exacerbation of underlying chronic longstanding illness. Both groups may be amenable to both additional nursing and other forms of community support to enhance self-care and continuity of care. Further research is required to increase our understanding of specific individual family and health system factors that predict repeat attendance in this age group.